Distributions of cadmium and lead levels in the intertidal clam Glauconome virens: a biomonitoring study - Yap, Chee Kong; Mat Rejab, Razeff Shardin; Cheng, Wan Hee; Kumar, Krishnan; H. Zakaly, Hesham M.; Okamura, Hideo; Horie, Yoshifumi; Sharifinia, Moslem; Keshavarzifard, Mehrzad; Naji, Abolfazl; Ismail, Mohamad Saupi; Ong, Meng Chuan (International Association of Advanced Materials, 2023)
The intertidal clam, Glauconome virens, was collected in the northwestern portion of Peninsular Malaysia near Kuala Perlis, Sungai Layar, and Pantai Teluk Air Tawar. This research attempted to determine the cadmium (Cd) and lead (Pb) concentrations in the various G. virenss organs. The Cd concentrations (mg/kg dry weight) in five distinct soft tissues ranged from 0.90 to 1.89, but the concentrations in shells ranged from 0.95 to 1.25. Pb concentrations (mg/kg dry weight) in the five distinct soft tissues ranged from 27.0 to 44.9, whereas shell concentrations ranged from 74.8 to 75.3. In general, the shell had more Pb than the soft tissue components. Future biomonitoring research on this type of clams should concentrate on certain tissues (such as the remainder, shell, and gill) to identify their potential as biomonitoring organs/materials. This biomonitoring study is of paramount importance to establish the intertidal clams as a good biomonitor under the umbrella of International Mussel Watch. Besides, establishment of such biomonitoring baseline data is important for future references and human health risk assessments.